Factors Affecting Premarital Sexual Behavior - Rahmawati Wae (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
ABSTRACT. Adolescence is a developmental phase between childhood and adulthood. During this period, physical and psychological changes oscur. Physical changes occur during the puberty period, especially the maturity of the sexual organs and hormonal changes, resulting in the emergence of sexual urgens in adolescents. Teenagers tend to want to try something new, including premarital sexual behavior in order to prove themselves. This type of research is quantitative descriptive. The population and sample in this research are 34 teenagers. The data collection technique in this research used an instrument with a Likert scale. The data obtained in this research will be analyzed using the percentage formula. The result showed that the description of adolescent premarital behavior in the high category with a percentages of 47%. Factors that influence the occurrence of adolescent premarital behavior for the biological dimension are categorized as high enough with a percentage of 41.17%, the psychological dimension is classified in fairly high category with a percentage of 32.3%, then the social dimension is also quite high with a percentage of 53%, and lastly from the moral cultural dimension it belongs to the very high category with percentage of 50%.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//